Вплив цифрової економіки на зменшення негативних наслідків соціального ризику - Білик, О. І.; Bilyk, O. (Видавництво Львівської політехніки, 2019)
Досліджено основні тенденції розвитку цифровізації економіки. Підкреслено зменшення впливу цифровізації економіки на соціальні ризики, зокрема охарактеризовано види структурних змін на ринку праці. Визначено дивергентні позиції працівників та роботодавців та виокремлено місце вмотивованості й гнучкості працівників і роботодавців в умовах цифровізації економіки.

The main tendencies of development of digitalization of economy are investigated in the article. Socio-economic changes affect the rapid implementation of new technologies. The reasons underlying such changes are multifaceted and complex, but they affect individual, social and economic needs and place new demands on the level of skill of employees and change the structure of the labor market. Therefore, the author substantiates the need to reduce the impact of digitalization of the economy on social risks. The digital economy has undergone dramatic changes in all aspects of business and commerce over the last two decades. These changes are far more significant than the development of information and communication technologies that have greatly facilitated the digital economy itself. Each business sector has undergone changes in its competitive market structure, consumer preferences, buying habits, marketing and advertising strategies, manufacturing operations, internal administration systems, supply chain mechanisms, and the opening up of the global economy, leading to diminished demand for a range of competencies and other professional skills, knowledge and skills of employees. In particular, the article describes the types of structural changes in the labor market. The divergent positions of workers and employers have been identified and the place of motivation and flexibility of workers and employers in the conditions of digitization of the economy has been identified. Based on analysis of hourly income of workers using the appropriate platforms in comparison with the level of average hourly wages in the economy, the impact of retraining workers of industrial professions on the gross regional product of the Lviv region was investigated.
The impact of the digital economy on the reduction of negative consequences of social risk
Keywords: цифровізація економіки; соціальний ризик; ринок праці; оплата праці; digitization of economy; social risk; labor market; remuneration; 331.101.5